Immigrant Self-employment: Definitions, Concepts and Methods - Nestorowicz, Joanna (Central and Eastern European Migration Review, 2012)
The paper presents a review of selected definitional issues and theoretical concepts related to the phe-nomenon of immigrant self-employment. A chronological analysis of the developments of the academic discourse on the topic allows detecting the interconnections between various approaches and under-standing their growing complexity. The inquiry is complemented with a review of most recent empiri-cal studies, what enables an assessment of the applicability and usefulness of long-established concepts for framing contemporary studies. Based on the appraisal of gathered material this paper also points to the limitations and possible areas of development of future research in the field.
Keywords: ethnic enclave; ethnic entrepreneurship; middleman minority; migration; self-employment